2015
DOI: 10.4209/aaqr.2014.11.0279
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Source Characterization of Submicron Particles at Residential and Traffic Sites in the Helsinki Metropolitan Area, Finland

Abstract: Chemical characterization of non-refractory submicron particles (NR-PM 1 ) and source apportionment of organic aerosols (OA) were carried out at four different sites in the Helsinki metropolitan area, Finland, using an Aerodyne Aerosol Chemical Speciation Monitor (ACSM). Two of the sites represented suburban residential areas, whereas the other two were traffic sites, one in a curbside in downtown and the other one in a suburban highway edge. The residential and the curbside measurements were conducted during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 51 publications
0
28
3
Order By: Relevance
“…The speed limit on Ring I was 80 km h −1 . The Helsinki Region Environmental Services Authority (HSY) had an air quality monitoring station at Malmi, and the chemical composition and sources of PM 1 at this site have been discussed earlier in Aurela et al (2015).…”
Section: Measurement Sites and Sampling Strategymentioning
confidence: 99%
“…The speed limit on Ring I was 80 km h −1 . The Helsinki Region Environmental Services Authority (HSY) had an air quality monitoring station at Malmi, and the chemical composition and sources of PM 1 at this site have been discussed earlier in Aurela et al (2015).…”
Section: Measurement Sites and Sampling Strategymentioning
confidence: 99%
“…A collection efficiency of 0.5 was assumed based on previous studies conducted on SMEAR III station, e.g. Aurela et al (2015). During the measurement period presented here the PM concentrations exhibited a mean average of 16.2 µg m −3 .…”
Section: Helsinki Finlandmentioning
confidence: 99%
“…The limited mass resolving power of the ETOF-equipped ToF-ACSM precludes the calculation of the oxidation state (see Kroll et al, 2011) and O / C and H / C ratios using the elemental analysis approach commonly employed in HR-ToF-AMS analysis and detailed in Aiken et al (2007) and Canagaratna et al (2015). However, it was recently shown that molecular and bulk chemical information can be extracted from series of complex mass spectra with limited mass resolution using a method developed by Stark et al (2015).…”
Section: Oxidation State From Analysis Of Mass Excessmentioning
confidence: 99%
See 1 more Smart Citation
“…Airborne particles consist of diverse composition including nitrates, sulfates, elemental and organic carbon, polycyclic aromatic hydrocarbons (PAHs), biological compounds, and metals (Cheruiyot et al, 2015;Kim et al, 2015), which causes severe impacts on climate and human health (Li et al, 2015), fine particles have been extensively studied in diverse fields (Aurela et al, 2015;Malaguti et al, 2015). Among them, the charging process of particles plays an essential part in many applications.…”
Section: Introductionmentioning
confidence: 99%